Monetary policy and hysteresis in potential output - Daniel Kienzler; Kai Daniel Schmid (University of Tübingen, Faculty of Economics and Social Sciences, 2013)
We show that actively stabilizing economic activity plays a more prominent role in the conduct of monetary policy when potential output is subject to hysteresis. We augment a basic New Keynesian model by hysteresis in potential output and contrast simulation outcomes of this extended model to the standard model. We find that considering hysteresis allows for a more realistic propagation of macroeconomic shocks and persistent movements in output after monetary shocks. Our central policy implication of active output gap stabilization arises from stability analyses and welfare considerations.
urn:nbn:de:bsz:21-opus-67993
Keywords: E32; E50; E52; 330; Monetary Policy; Hysteresis; Potential Output; Output Gap Mismeasurement